The unanticipated road to skills wastage for skilled migrants: the non-recognition of overseas qualifications and experience (ROQE). (2nd January 2019) - Cameron, Roslyn; Farivar, Farveh; Dantas, Jaya
ABSTRACT: Skilled migration has become a significant strategy for meeting skill demands and shortages in Australia; however, many skilled migrants experience barriers to securing employment which creates an array of social and economic insecurities and vulnerabilities. Those whose overseas qualifications and work experience are not recognised in host countries will often experience skill wastage and atrophy and exploitation. The recognition of overseas qualifications and experience (ROQE) has been identified as a 'central immigration issue of the new century … in all post-industrial societies receiving immigrants'. For many skilled migrants, ROQE creates a barrier for securing employment commensurate with qualifications and experience and thereby creates skills wastage and downward mobility. The aim of this paper is to analyse ROQE through the dual theoretical lenses of human capital theory and the critical analyses of knowledge hierarchies. Data from a survey of skilled migrants in Western Australia are used to compare the occupations of skilled migrants prior to entering Australia and their current occupation. The paper offers a dual lens theoretical analysis of the problematic ROQE phenomenon and concludes with policy- and practice-based strategies that would assist in reducing skills wastage and the exploitation of skilled migrants.